Docência universitária: repensando a prática do professor de educação física - Silva, Sarah Maria Freitas Machado (2008)
This research has as object of study the university teaching, mainly in the courses of Licentiate ship in Physical Education arising two central problems: 1. How is the pedagogic Physical Education teacher practice happening? 2. How is Physical Education teacher performing in the course of Licentiateship in Physical Education with elements of the teachers knowledge, the demands of work in the Superior Teaching and with the current universitary pedagogical concepts. Starting from these problems, this work aims at discussing the pedagogic Physical Education university teacher practice seeking to understand how this teacher performs with elements of the teachers knowledge, the demands of work in the Superior Teaching and with the current universitary pedagogical concepts. In relation to the general theoretical approach of the university teaching some authors are highlighted: Cunha (2006); Malusá (2005); Morosini (2001); Pachane (2004); Pimenta (2005), among others and specifically in Physical Education: Caparróz (2007); Lacerda (2007); Souza Neto (2007); Taffarel (2004). This dissertation comprises four chapters. The first University Teaching the making of teacher identity in the Superior Teaching, has specific goals: to present some considerations about University and to discuss the formation and performing university teacher, tying teachers knowledge to the demand of work in the universitary teaching and the current pedagogical conceptions. The second chapter, the Physical Education teacher in the university teaching: challenges and dilemmas , discusses about the path followed by the Physical Education course and discusses the formation of the Physical Education professional, joining universitary pedagogical conceptions. The third chapter The Methodological Paths presents the locus of the research, the subjects, propose a quanti-qualitative approach as methodology and as tool, the Inventário Adaptado Proal. The fourth chapter presents the statistic tabulated data analysed and interpreted from the confrontation with the theoretical approach verifying the existence or not of the correlation statistically significant between the independent and the questionnaire items. Its is presented in the field research the results of the participation of 25 teachers graduated in Physical Education and mainly in the course of Licentiate ship in Physical Education. The place of the research was in a SIE located in the Central-West region in the city of Goiânia/Goiás. A semi-structured questionnaire with 23 questions validated as Inventário Adaptado Proal, in the quanti-qualitative analyse perspective. As a result, it was verified in the data that the teachers always articulate the teachers knowledge with their practice which represents a knowledge valorization in the formation of teachers. It was observed that the universitary teachers when questioned about how they articulated their teaching practice with the demands of productivity in graduation and post-graduation field, the majority never or almost never articulate this situation. The majority of data also presents that the teachers always and almost always, that the teachers show to their students other points of view about the studied theme. Another aspect is that the majority of the teachers always updates the theoretical approach which points that the teacher is pedagogically prepared to be teachers.